Faktor-Faktor yang Mempengaruhi Pendapatan Nelayan Di Kabupaten Tanjung Jabung Barat - Samsiyah Samsiyah (Science of Management and Students Research Journal (SMS), 2019)
Income is the amount of goods and services that meet the level of life of the community, where the existence of income owned by the community can fulfill their needs. This study aims to determine how much factors influence the income of fishermen in Tanjung Jabung Barat District.  Based on the results of the MSS analysis tool that the authors get the results of the research in the form of capital variables have a negative influence on the income of fishermen in West Tanjung jabung regency because the t-count value for X1 (capital) is - 8,784 while for t-table with a 0.05 level of trust ( = 5%) is 1,985 because the t-count value is smaller than t-table (- 8,784 <1,985), then Ho is accepted and means the value of capital does not have a positive effect but with a significant level (0,000 <0,05) of income fishermen in Tanjung Jabung Barat District. While X2 (technology) is 2.829 while for t-table with a confidence level of 0.05 (α = 5%) is 1.985 because the value of t-count is greater than t-table (2.829> 1.985), then Ho is rejected and means significant technological value to the income of fishermen in Tanjung Jabung Barat District. While X3 (work experience) is - 0.229 while for t-table with a confidence level of 0.05 (α = 5%) is 1.985 because the t-count value is greater than t-table (- 0.229 <1.985), then Ho in accept and means that the value of work experience does not have a significant effect on the income of fishermen in Tanjung Jabung Barat District. While X4 (distance traveled by sea) is 1,396 while for t-table with a confidence level of 0.05 (α = 5%) is 1,985 because the value of t-count is greater than t-table (1,396 <1,985), then Ho is accepted and means that the value of the sea-going distance does not have a significant influence on the income of fishermen in the West Tanjung Jabung Regency. Based on the F test together with a confidence level of 95%, it is obtained F-count (32.907> 2.47), which means accepting Ha and Ho being rejected. This shows that together the independent variables influence the income of fishermen in Tanjung Jabung Barat District. From the results of the analysis in this study, it can be concluded, that the technologist has a positive and significant influence on the income of fishermen in the western Tanjung Peninsula district. And capital does not have a positive influence but is significant on the income of fishermen in the west headland district. Whereas work experience and distance traveled to the sea does not affect the income of fishermen in the west Tanjung tanjung regency.